EVALUASI KEBIJAKAN PENGELOLAAN SAMPAH OLEH DINAS LINGKUNGAN HIDUP DI KABUPATEN GAYO LUES PROVINSI ACEH TAHUN 2021 - Amaysah amaysah; Ngadisah Ngadisah; Dahlan A. Rahman (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The aim of this research is to evaluate waste management policies by comparing policy objectives/targets with the results achieved. Gayo Lues Regency is one of the districts in Aceh Province. This type of research is descriptive with a qualitative approach. The problem currently faced in waste management is that waste management is not yet optimal, both in terms of services, operational and maintenance costs, institutions, regulations and community participation in its management. The theories used are evaluation theory and management dimensions. Researchers use a qualitative descriptive research design, to understand phenomena about what research subjects experience, for example behavior, perceptions, motivations, actions, etc. holistically, and by means of descriptions in the form of words and language, in a specific context. naturally and by utilizing various natural methods. The results of research on the Evaluation of Waste Management Policies at the Gayo Lues Regency Environmental Service show that the implementation of waste management in Gayo Lues Regency has not been effective, which can be seen from the planning system which is not evenly distributed across all sub-districts in Gayo Lues Regency, and has not been able to carry out waste clean-up activities. , and the waste bank program has not yet run as expected. This is because there are still obstacles, namely limited budget, human resources, and waste management facilities and infrastructure.